Linear and nonlinear optical efficiency of novel neodymium nanoparticles doped tellurite glass for advanced laser glass - Azlan M.N. (Universiti Pendidikan Sultan Idris, 2018)
Linear and nonlinear optical efficiency of novel neodymium nanoparticles doped tellurite glass for advanced laser glass by Azlan M.N.